Iksan Kamil Sahri's Perspective on Dualism of the Education System in Indonesia - Karimullah, Suud Sarim; Wati, Tita Pertama; Najib, Ainun; Wahyudi, Wahyudi (Green Publisher Indonesia, 2023)
This study discusses the dualism of the education system in Indonesia from the perspective of Iksan Kamil Sahri, a pesantren anthropologist and one of the most productive young scholars. He explained the massification of pesantren, such as the institutionalization of pesantren, which is firmly rooted amid society with various challenges. In collecting data, this study uses library research with qualitative methods emphasizing meaning through a qualitative naturalistic approach using content analysis. The final result of this study states that the educational dualism that occurs creates a value crisis in human civilization that considers science to be value-free, so the impact of scholastic duality is the decline of Islamic educational institutions that do not emphasize mastery of empirical knowledge, even though in terms of morality it can maintain the value system and scientific disciplines classical science. Meanwhile, public educational institutions emphasizing practical knowledge are very fragile regarding religious knowledge. In addition, the disparity stated by Iksan Kamil Sahri between pesantren and general education, which is managed differently by the two ministries in Indonesia, is due to the different educational objectives that exist between the two. Pesantren education aims to make graduates religious experts, while national education in Indonesia aims to produce graduates who meet industry standards to be ready for work.